Fluvastatin promotes chondrogenic differentiation of adipose-derived mesenchymal stem cells by inducing bone morphogenetic protein 2 - Masanari Kuwahara; Yukio Akasaki; Norio Goto; Ichiro Kurakazu; Takuya Sueishi; Masakazu Toya; Taisuke Uchida; Tomoaki Tsutsui; Ryota Hirose; Hidetoshi Tsushima; Yasuharu Nakashima (BMC, 2022)
Abstract Background Adipose-derived mesenchymal stem cells (ADMSCs) are a promising source of material source for medical regeneration of cartilage. Growth factors, including transforming growth factor-β (TGFβ) subfamily members and bone morphogenetic proteins (BMPs), play important roles in inducing and promoting chondrogenic differentiation of MSCs. However, these exogenous growth factors have some drawbacks related to their cost, biological half-life, and safety for clinical application. Several studies have reported that statins, the competitive inhibitors of 3-hydroxy-2-methylglutaryl coenzyme A (HMG-CoA) reductase, induce the expression of BMP2 in multiple cell types as the pleotropic effects. The objective of this study was to investigate the effects of fluvastatin during chondrogenic differentiation of human ADMSCs (hADMSCs). Methods The effects of fluvastatin were analyzed during chondrogenic differentiation of hADMSCs in the pellet culture without exogenous growth factors by qRT-PCR and histology. For functional studies, Noggin, an antagonist of BMPs, mevalonic acid (MVA) and geranylgeranyl pyrophosphate (GGPP), metabolites of the mevalonate pathway, ROCK inhibitor (Y27632), or RAC1 inhibitor (NSC23766) were applied to cells during chondrogenic differentiation. Furthermore, RhoA activity was measured by RhoA pulldown assay during chondrogenic differentiation with or without fluvastatin. Statistically significant differences between groups were determined by Student's t-test or the Tukey-Kramer test. Results Fluvastatin-treated cells expressed higher levels of BMP2, SOX9, ACAN, and COL2A1 than control cells, and accumulated higher levels of glycosaminoglycans (GAGs). Noggin significantly inhibited the fluvastatin-mediated upregulation of ACAN and COL2A1. Both MVA and GGPP suppressed the effects of fluvastatin on the expressions of BMP2, SOX9, ACAN, and COL2A1. Furthermore, fluvastatin suppressed the RhoA activity, and inhibition of RhoA-ROCK signaling by Y27632 increased the expressions of BMP2, SOX9, ACAN, and COL2A1, as well as fluvastatin. Conclusions Our results suggest that fluvastatin promotes chondrogenic differentiation of hADMSCs by inducing endogenous BMP2, and that one of the mechanisms underlying the effects is inhibition of RhoA-ROCK signaling via suppression of GGPP. Fluvastatin is a safe and low-cost compound that holds promise for use in transplantation of hADMSCs for cartilage regeneration.